triple brackets
expand and simplify

Answer:
x^3+10x^2+31x+30
Step-by-step explanation:
(x + 5)(x +2) (x+3)
(x^2+7x+10) ( x + 3 )
=x^3+ 10x^2+ 31x +30
// apreciate if marked as brainliest//
Answer:
x³ + 10x² + 31x + 30
Step-by-step explanation:
Volume = (x +5)*(x + 2) * (x + 3)
= (x + 5) * [ x*(x+3) + 2*(x +3]
= (x + 5) * [x*x + x*3 + 2*x + 2*3]
= (x +5) *[x² +3x + 2x + 6] {Combine like terms}
= (x +5) (x² + 5x + 6)
= x *(x² + 5x + 6) + 5*(x² + 5x + 6)
= x*x² + x*5x + x*6 + 5*x² +5*5x + 5 *6
= x³ + 5x² + 6x + 5x² + 25x + 30
= x³ + 5x² + 5x² + 6x + 25x + 30
= x³ + 10x² + 31x + 30